Exciplex emissive supramolecular polymer formed by tuning molecular conformation. Issue 32 (12th August 2020) - Heo, Sojeong; Kim, Ka Young; Choi, Heekyoung; Kang, Seok Gyu; Choi, Wonjin; Lee, Shim Sung; Jung, Sung Ho; Jung, Jong Hwa
Abstract : The strong exciplex emission of the supramolecular polymer I with yellow emission was a consequence of the intramolecular charge transfer interactions in a mixed DMSO/H2 O (60 : 40–1 : 99 v/v) solution. Abstract : We demonstrated the exciplex emission of supramolecular polymers (Bipy-1 ) possessing bipyridine and pyrene moieties. The distinctive exciplex emission of the supramolecular polymers was controlled by tuning the molecular conformation in different composition ratios of a mixed DMSO/H2 O solution. The strong exciplex emission of the supramolecular polymer I with yellow emission was a consequence of the intramolecular charge–transfer interactions in a mixed DMSO/H2 O (60 : 40–1 : 99 v/v) solution.